Trends in Poliovirus Seroprevalence in Kano State, Northern Nigeria. (30th October 2018) - Verma, Harish; Iliyasu, Zubairu; Craig, Kehinde T; Molodecky, Natalie A; Urua, Utibeabasi; Jibir, Binta Wudil; Gwarzo, Garba Dayyabu; Gajida, Auwalu U; McDonald, Sharla; Weldon, William C; Oberste, M Steven; Braka, Fiona; et al.
Abstract: Background: Kano state has been a protracted reservoir of poliovirus in Nigeria. Immunity trends have been monitored through seroprevalence surveys since 2011. The survey in 2015 was, in addition, intended to assess the impact of use of inactivated poliovirus vaccine (IPV). Methods: It was a health facility based seroprevalence survey. Eligible children aged 6-9, 12-15 and 19-22 months of age brought to the paediatrics outpatient department of Murtala Mohammad Specialist Hospital between 19 October and 6 November 2015, were screened for eligibility. Eligible children were enrolled after parental consent, history taken, physical examination conducted, and a blood sample collected to test for neutralizing antibody titres against the three poliovirus serotypes. Results: Overall, 365 results were available in the three age groups. In the 6-9-month-old age group, the seroprevalence was 73% (95% confidence interval [CI] 64-80%), 83% (95% CI 75-88%), and 66% (95% CI 57-73%) for serotypes 1, 2, and 3, respectively. In the 12-15- and 19-22-month-old age groups, seroprevalence was higher but still remained <90% across serotypes. Seroprevalence to serotypes 1 and 3 in 2015 was similar to 2014; however, for serotype 2 there was a significant improvement. IPV received in supplemental immunization activities was found to be a significant predictor of seropositivity among 6-9-month-old infants for serotypes 1 and 2. Conclusions: Seroprevalence for serotypes 1 and 3 remains low (<80%) in 6-9-month-olds. This poses a significant risk for poliovirus spread if reintroduced into the population. Efforts to strengthen immunization coverage are imperative to secure and sustain high population immunity.